2022
DOI: 10.47278/journal.ijvs/2022.204
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Nutrient Digestibility and Ruminal Fermentation Characteristics of Ammoniated and Fermented Treatment of Soaked and Unsoaked Cymbopogon nardus Waste

Abstract: Cymbopogon nardus waste has potential as an ingredient of cattle diet. C. nardus waste requires feed processing to increase ruminal fermentation characteristics. This study has aimed to discover the effect of fermentation and ammoniation treatment of soaked and unsoaked C. nardus on in vitro ruminal fermentation characteristics and nutrient digestibility. Five experimental diets with four replications were evaluated in this study: Cymbopogon nardus (CNW) as control, unsoaked fermented CNW (FCNW1), soaked ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
3
1
1
Order By: Relevance
“…The pattern of OMD is linear with DMD because it constitutes the largest component of DM. This linear pattern has been previously observed by Antonius et al (2023); Elihasridas et al (2023a). The organic material components in the A1B2 treatment are more easily degraded by rumen microbes, resulting in higher OMD than other treatments.…”
Section: Digestibility Of Dry Matter Organic Matter and Crude Proteinsupporting
confidence: 83%
“…The pattern of OMD is linear with DMD because it constitutes the largest component of DM. This linear pattern has been previously observed by Antonius et al (2023); Elihasridas et al (2023a). The organic material components in the A1B2 treatment are more easily degraded by rumen microbes, resulting in higher OMD than other treatments.…”
Section: Digestibility Of Dry Matter Organic Matter and Crude Proteinsupporting
confidence: 83%
“…Based on the results of the first phase of the study, it was found that the crude fiber content decreased with increasing immersion time with betel lime. With lower levels of crude fiber, it will be more easily digested by enzymes produced by rumen microbes, so as to increase the digestibility value of fiber (Jamarun et al 2017b;2017c;Elihasridas et al 2023). However, in this study the digestibility value of the fiber decreased with increasing betel lime dose.…”
Section: Crude Fiber Digestibility Of Cassava Peelcontrasting
confidence: 54%
“…Pazla et al (2020;2021d;2023c) states that the low crude fiber content in the feed will make it easier for rumen microbial enzymes to penetrate into the feed material for the digestion of food substances. The digestibility of feed is impacted by its chemical composition, and the proportion of fibrous feed significantly affects nutrient digestibility (Jamarun et al 2017c;Yanti et al 2021;Elihasridas et al 2023b).…”
Section: Treatment Of Digestibility In Etawa Crossbreed Dairy Goatsmentioning
confidence: 99%